Cecilia - Becker, Will. L.; O'Hare, William Christopher; State Theatre (Sydney, N.S.W.) (1900)
Part of the State Theatre collection of cinema scores and parts, mainly used for silent movies, but including musical materials associated with talking pictures ca. 1900-1950, used by the State Theatre and various film distribution companies throughout Australia. Some items include performance annotations.
Stamped: West's Pictures Limited.
The stamped marking on the material indicates the film distribution companies or theatres that owned, used, or distributed the music to other cinemas.
Keywords: Dramatic music; Instrumental music -- Scores and parts; Silent film music